PENGEMBANGAN PERANGKAT PEMBELAJARAN PADA MATERI GEOMETRI DAN PENGUKURAN DENGAN PENDEKATAN PENDIDIKAN MATEMATIKA REALISTIK INDONESIA DI SD NEGERI 179 PALEMBANG - N. Fahriza Fuadiah; Zulkardi Zulkardi; Cecil Hiltrimartin (Jurnal Pendidikan Matematika, 2009)
The aims of the research is to produce the set of oriented realistic mathematical education (RME) approach material that is valid and practical for teaching in elementary school student of the fifth grade and have a good potencial effect. PMRI is one of learning approach which dribbles students in understanding mathematics concept by selfcontruction through prior knowledge which is related to daily activity, finding the concept by themselves so that the learning becomes meaningful. The research is a development research and method used in two stages, that are preliminary study (analysis and model development stage) and formative study (evaluation and revision stage). The samples were students of fifth grade at SD Negeri 179 Palembang. In technique collecting the data, the writer used interview with the experts, observation by using prototype. The data was analyzed by using descriptive method. The result of data analyses concludes that the development of geometry and measurement prototype for the fifth grade students is valid based on content, construction, and language. It can be conclude from the documentary data that the use of student’s book has been a practical use. The try out tested on students has given potential effect which is the students like to study using realistic mathematical education approach with student activity level of 6.47 in a very high criteria and the average of final mark of 87,17 in a very good criteria. Key words: development research, RME, the set of teaching and learning